Creaturalità: Celan e Valéry - Massimo Baldi (Aisthesis, 2012)
Subject of this essay is the relationship between Celan’s and Valéry’s theory on language, aesthetic and history. Resorting to the importance of some passages of Valéry’s Cahiers for the conception of Celan’s theoretical doctrine of the poetry, the author underwrites the centrality of this philosophical heritage for the explanation and the justification of Celan’s linguistic choices and of their historical and political meaning.